The lower animals living invertebrates of the world - Buchsbaum, Ralph; Milne, Lorus J. (Garden City, N.Y. Doubleday, 1960)
A guide to invertebrates. The authors describe the different families of these animals without a spine, their lives and characteristics.
Bibliography: p. 291-292.
Keywords: Invertebrates